The Effect of Acupressure Therapy on Blood Pressure At Hypertension Patient - Galih Jatnika; Teguh Akbar Budiana; Yuswandi Yuswandi (MEDIA ILMU KESEHATAN, 2022)
Introduction: Hypertension is a chronic disease characterized by an increase in systolic and diastolic blood pressure above 140/100 mmHg. Hypertension with not controlled management will have an impact on the emergence of various complications including stroke, kidney failure, heart disease. Currently conventional therapy for hypertension uses drugs such as captopril, but continuous drug administration can cause adverse side effects from the drug. Acupressure therapy is a relatively inexpensive complementary therapy and tends not to have side effects like chemical drugs. Objective: This study aims to identify the effect of acupressure therapy on blood pressure in hypertensive clients. Methods: The research method used is pre-experimental. Respondents who participated in this study were 12 respondents who were residents at Kelurahan Utama, Kecamatan Cimahi Selatan. Acupressure therapy is given by massage using fingers at points ST 36, LR 3, Li 4 for 30 minutes with a massage strength of 3 kg. Furthermore, the data were analyzed using the wilcoxon test. Results: The results showed that the mean systolic and diastolic blood pressure before treatment was 153.33/94.17 mmHg, systolic and diastolic blood pressure after treatment was 142.83/88.50 mmHg. Conclusion: There is an effect of acupressure therapy on reducing blood pressure (p value = 0.006) in hypertensive clients. It is recommended for hypertensive clients to continue acupressure therapy in an effort to reduce high blood pressure